Urban regeneration and the environmental challenge joint triennial conference 1993. (Thomas Telford, 1993)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of the joint ICE/ASCE/CSCE triennial conference held in September 1993.